Indek’s DMF-T dengan Kejadian Anemia pada Remaja Putri Berdasarkan Status Gizi - Rusmali Rusmali (Poltekkes Kemenkes Kupang, 2019)
Abstract: DMF-T index with the incidence of anemia in adolescent girls based on nutritional status. The DMF-T index in Indonesia based on the results of 2013 basic health research nationally reached 4.6 which means that everyone has dental and oral health cases such as cavities, missing teeth removed by caries and there are still good fillings, as many as 5 cases. West Kalimantan Province, the DMF-T index reached 6.2 or 7 cases. Tooth decay in adolescents as the next generation is very disturbing in the mastication process, which can reduce the intake of nutrients into one's body. If this event continues from an early age to adolescence and adulthood, it can cause a decrease in the quantity of red blood cells in the circulation or the amount of hemoglobin is below normal limits. The lack of hemoglobin in the blood can interfere with growth and development, to the nutritional status. The area of ​​Pontianak City is 107. 82 km2 with a population of 607,438 people, and the target of teenagers who have been screened in 2018 in November was 97.779 people. The purpose of this study was to describe the DMF-T index, the incidence of anemia by looking at the nutritional status of adolescent girls, as well as looking at the relationship of these variables. This type of research is descriptive research with explanatory research. How to take samples with random side, univariate analysis, bivariate with correlation regression test. The results showed the DMF-T index in young women in the Khatulistiwa Health Center in Pontianak Utara District Pontianak City was very low (0.0-1.0) as much as 36.4%, the incidence of anemia as normal as much as 77.3% and nutritional status (BMI / BW: TB2) the average thin (<18.4 kg / m2) is 59.1%. The conclusions of this study indicate that the index of DMF-T is very low (36.4%) and is not related to nutritional status because the cnification value is 0.13> from 0.05, the incidence of anemia is normal (77.3%) but is highly related to nutritional status because the value of cnification 0.01 <from 0.05, while the nutritional status of the average thin (<18.4 kg / m2) is 59.1%. Absrak: Indek’s DMF-T dengan Kejadian Anemia pada Remaja Putri Berdasarkan Status Gizi. Indek’s DMF-T di Indonesia berdasarkan hasil riset kesehatan dasar tahun 2013 secara Nasional mencapai 4,6 yang artinya setiap orang mempunyai kasus kesehatan gigi dan mulut seperti gigi berlubang, gigi hilang dicabut oleh karena karies dan terdapat tambalan yang masih baik yaitu sebanyak 5 kasus. Provinsi Kalimantan Barat, Indek’s DMF-T mencapai 6,2 atau 7 kasus. Kerusakan gigi pada remaja sebagai generasi penerus sangat mengganggu dalam proses pengunyahan, yang berakibat dapat mengurangi asupan gizi kedalam tubuh seseorang. Kejadian tersebut apabila berlanjut dari usia dini sampai remaja dan dewasa, maka dapat menyebabkan penurunan kuantitas sel-sel darah merah dalam sirkulasi atau jumlah hemoglobin berada dibawah batas normal. Kurangnya jumlah hemoglobin dalam darah dapat mengganggu pertumbuhan dan perkembangan, sampai pada status gizi kurang. Luas wilayah Kota Pontianak 107. 82 km2 dengan jumlah penduduk 607.438 jiwa, dan sasaran remaja yang sudah mendapat diskrening di tahun 2018 bulan November tercatat sebanyak 97.779 orang. Tujuan penelitian ini adalah untuk mendeskripsikan Indek’s DMF-T, kejadian anemia dengan melihat status gizi remaja putri, serta melihat keterkaitan dari variabel tersebut. Jenis penelitian ini adalah penelitian deskriptif dengan penelitian explanatory research. Cara pengambilan sampel dengan random samping, analisa univariat, bivariat dengan uji regresi korelasi. Hasil penelitian menunjukkan indek’s DMF-T pada remaja putri diwilayah Puskesmas Khatulistiwa Kecamatan Pontianak Utara Kota Pontianak adalah rendah sekali (0,0-1,0) sebanyak 36,4%, kejadian anemia rata-rata normal sebanyak 77,3% dan status gizi (IMT/BB:TB2) rata-rata kurus (< 18,4 kg/m2) yaitu sebanyak 59,1%. Simpulan penelitian ini menunjukkan bahwa indek’s DMF-T rendah sekali (36,4%) dan tidak berhubungan dengan status gizi karena nilai siknifikasi 0,13 > dari 0,05, kejadian anemia normal (77,3%) tetapi sangat berhubungan dengan status gizi karena nilai siknifikasi 0,01 < dari 0,05, sedangkan status gizi rata-rata kurus (< 18,4 kg/m2) yaitu 59,1%.